Prognostic Role of Ammonia in Critical Care Patients Without Known Hepatic Disease - Zhao, Lina; Walline, Joseph Harold; Gao, Yanxia; Lu, Xin; Yu, Shiyuan; Ge, Zengzheng; Zhu, Huadong; Li, Yi (Frontiers in Medicine, 2020)
Background&Amis: Hyperammonemia usually develops because of hepatic disease, but it may occur in patients with non-hepatic hyperammonemia (NHH). But, studies on the prognosis and possible risk factors of this disorder are lacking. The aim of this study was to find possible prognostic and risk factors for NHH in critically ill patients. Methods: Data were extracted from MIMIC III Database. Survival was analyzed by the Kaplan-Meier method. Univariate and multivariate analyses were performed to identify prognostic factors. Results: Valproic acid, carbamazepine, corticosteroids, recent orthopedic surgery, epilepsy, disorders of urea cycle metabolism, and obesity were found to be risk factors for NHH. Patients in the hyperammonemia group had a higher 30-day mortality than those in the non-hyperammonemia group. After final regression analysis, ammonia was found to be independent predictors of mortality. Conclusion: Ammonia was an independent prognostic predictor of 30-day mortality for critical care patients without liver disease.